Use of virtual reality for pre-surgical planning in separation of conjoined twins: A case report. (December 2019) - Juhnke, Bethany; Mattson, Alex R; Saltzman, Daniel; Azakie, Anthony; Hoggard, Eric; Ambrose, Matthew; Iaizzo, Paul A; Erdman, Arthur; Fischer, Gwenyth
We describe the use of virtual reality technology for surgical planning in the successful separation of thoracopagus conjoined twins. Three-dimensional models were created from computed tomography angiograms to simulate the patient's anatomy on a virtual stereoscopic display. Members of the surgical teams reviewed the anatomical models to localize an interatrial communication that allowed blood to flow between the two hearts. The surgical plan to close the 1-mm interatrial communication was significantly modified based on the pre-procedural spatial awareness of the anatomy presented in the virtual visualization. The virtual stereoscopic display was critical for the surgical team to successfully separate the twins and provides a useful case study for the use of virtual reality technology in surgical planning. Both twins survived the operation and were subsequently discharged from the hospital.